2012
DOI: 10.1177/0363546512443050
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Graft Maturity of the Reconstructed Anterior Cruciate Ligament 2 Years Postoperatively

Abstract: The allograft group had a significantly higher SNQ value compared with the autograft group in this study, indicating that allograft tendons might have inferior graft maturity than autograft tendons in ACL reconstruction at 2 years postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 30 publications
2
53
0
2
Order By: Relevance
“…44 , 57 , 71 , 74 Nineteen articles were excluded because they included patients of all ages and did not stratify their outcomes by age. 5 , 10 , 18 , 23 - 25 , 32 , 38 , 42 , 49 , 56 , 61 , 62 , 66 , 76 , 78 - 80 , 83 Twenty-one studies were excluded because duration of follow-up was less than 2 years. 1 , 13 , 14 , 31 , 35 , 39 - 41 , 43 , 51 , 52 , 58 , 65 , 70 , 73 , 75 , 84 , 87 , 89 - 91 Three studies were excluded because they did not report on failure (2 reported on muscle strength and 1 on transplantation safety).…”
Section: Resultsmentioning
confidence: 99%
“…44 , 57 , 71 , 74 Nineteen articles were excluded because they included patients of all ages and did not stratify their outcomes by age. 5 , 10 , 18 , 23 - 25 , 32 , 38 , 42 , 49 , 56 , 61 , 62 , 66 , 76 , 78 - 80 , 83 Twenty-one studies were excluded because duration of follow-up was less than 2 years. 1 , 13 , 14 , 31 , 35 , 39 - 41 , 43 , 51 , 52 , 58 , 65 , 70 , 73 , 75 , 84 , 87 , 89 - 91 Three studies were excluded because they did not report on failure (2 reported on muscle strength and 1 on transplantation safety).…”
Section: Resultsmentioning
confidence: 99%
“…Females were excluded because of different hormonal level, which might greatly influence graft maturity. One senior surgeon (S. Chen) performed all the operations using arthroscopic single-bundle ACL reconstruction techniques as described by Li et al 22 For the autograft reconstruction, the semitendinosus and gracilis tendons were harvested and prepared as a 4-strand double-looped hamstring autograft with a minimum of 12 cm in length. In the allograft group, a fresh-frozen tibialis anterior allograft tendon (Osteolink Biomaterial Co) was thawed in sterile physiologic fluid at room temperature and prepared as a 4-strand double-looped graft similar to the autograft.…”
Section: Methodsmentioning
confidence: 99%
“…The SNQ of each graft site (femoral-adjacent, middle, and tibial-adjacent) was estimated using the following equation: SNQ = (signal of ACL graft − signal of quadriceps tendon)/signal of background ( Figure 1 ). 22 The SNQ value of the graft was calculated by averaging the SNQ value of the 3 sites. In addition, the sagittal ACL angle and the ACL–Blumensaat line angle were measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…На сегодня в литературе недостаточно информации относительно МРТ-характеристик интеграции аутотрансплантата из сухожилий полусухожильной и нежной мышц в костном канале у пациентов, которым выполнено восстановление ПКС [7,9,11,13]. Магнитно-резонансная томография (МРТ) -это метод исследования, который дает возможность оценить состояние интеграции трансплантата на границе «сухожилиекость», а также определить интенсивность сигнала от трансплантата в костном канале.…”
unclassified